Develop Innovative Thinking Skills Based on a Creative Approach - Kadirova Dildora Najatbekovna (Research Parks Publishing LLC, 2021)
This article outlines the pedagogical foundations and guidelines for shaping a person’s creativity and creativity in it. What theoretically focuses on the formation of innovative thinking skills in educators based on a creative approach